Корпусный подход в современных исследованиях языковой вариативности - Перепечкина, С.Е. (Культура народов Причерноморья, 2014)
В статье рассматриваются возможности корпусного подхода в исследовании языка,
функционирующего в реальных условиях; указываются характеристики метода, определяющие его
надежность и достоверность. Основное внимание уделяется новейшим исследованиям социально и
территориально обусловленной вариативности немецкого языка в Северной Германии и
стилистической языковой дифференциации в виртуальных жанрах коммуникации; описываются
возможности электронных собраний текстов для использования их в научных целях. У статті розглядуються можливості корпусного підходу у дослідженні мови, що функціонує
в реальних умовах; указуються характеристики методу, які визначають його надійність і
достовірність. Основна увага приділяється новітнім дослідженням соціально и територіально
зумовленої варіативності мови у Північній Німеччині та стилістичної мовної диференціації у
віртуальних жанрах комунікації; описуються можливості електронних колекцій текстів для
використання їх з науковою метою. This article discusses the possibilities of corpus-based approach in the linguistic study, i.e. the study
of language as expressed in samples (corpora) of "real world" text. It introduces the basic aspects of this
approach – corpus representativeness and balance. Being “collections of naturally occurring language text”
(John Sinklair), corpora can provide a good basis for the study of language variation with the application of
new electronic technologies. The article focuses on the latest research of social and geographical variability of
language in Northern Germany as well as on the language differentiation in the virtual genres of
communication. With the fact a new spoken language variety, regarded as a contact variety (a result of High and
Low German contact), has become widespread in the Northern of Germany, a new research of language
situation in this area became necessary. The identification, description and analysis of language variation in
terms of regional, social and situational usage are the primary purpose of the SiN project (Sprachvariation in
Norddeutschland). Documenting object language data along with the speakers' subjective opinions and
reflexions on language norm will allow for compiling the first ever text corpus of Low German substandard
dialect. On the bases of such a corpus a wide variety of socio- and idiolect research on phonetic, lexical and
grammatical level can be realized. Another actual problem today is the Internet-based communication and its
genres: e-mail, forums, web-chats and weblogs, Skype etc., so it becomes necessary to create balanced,
annotated corpora of computer-mediated communicaton such as the Dortmund Chat Corpus (ca. 500 annotated
chat-logs and a retrieval tool available online), whose resources can be used for studying of chat-stile in its
various forms.